Antistatic EVA foaming material and preparation method thereof

By synthesizing modified graphene in EVA foam materials, the problem of insufficient electrostatic, antibacterial and anti-aging properties of the material has been solved, efficient antistatic and comprehensive performance improvements have been achieved, and the application fields have been broadened.

CN119350757AInactive Publication Date: 2025-01-24QILI TECHNOLOGY (GUANGDONG) CO LTD

Patent Information

Application Number
CN202411585955.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Due to the high electrical insulation of existing EVA foaming materials, there are electrostatic problems in certain special application areas such as military weapons, electronic components, instruments, etc., which may lead to fires and lack antibacterial and anti-aging properties.

Method used

By synthetic graphene and combine it with other raw materials in the EVA foam material to prepare an anti -static EVA foam material. Modified graphene is prepared through multi -step chemical reactions. It has high -electricity and good interface compatibility. It can effectively reduce the static resistance of the material and give the material antibacterial and anti -aging performance.

Benefits of technology

The efficient anti -static performance, antibacterial performance, and anti -aging performance of EVA foam materials have been realized, their application areas have been broaden, the risk of static fires is avoided, and the comprehensive performance of the material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005124290440000021
    Figure BDA0005124290440000021
  • Figure BDA0005124290440000031
    Figure BDA0005124290440000031
  • Figure BDA0005124290440000032
    Figure BDA0005124290440000032
Patent Text Reader

Abstract

The invention discloses an antistatic EVA foam material and a preparation method thereof, and belongs to the technical field of polymer composite materials. The preparation method comprises the following steps: weighing 90-100 parts of EVA, 15-25 parts of an ethylene-octylene copolymer, 10-18 parts of modified graphene, 2-4 parts of a foaming agent, 0.5-1 part of a lubricant, 0.5-1 part of zinc oxide and 0.1-0.5 part of a cross-linking agent, mixing in an internal mixer, mixing in an open mill, pressing the materials into sheets, finally putting the sheets into a preheated plate vulcanizing machine mold cavity, and carrying out mold pressing foaming to obtain the antistatic EVA foaming material. The modified graphene contains a lipophilic long carbon chain and a benzene ring, so that the modified graphene has good compatibility with the remaining raw materials, and the modified graphene containing the graphene, the hindered phenol structure and the quaternary ammonium salt structure can be highly dispersed in the EVA foaming material and fully plays a role, so that the EVA foaming material disclosed by the invention has efficient and lasting antistatic performance, antibacterial performance and anti-aging performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer composite materials, and in particular relates to an antistatic EVA foam material and a preparation method thereof. Background Art

[0002] EVA is an ethylene-vinyl acetate copolymer obtained by copolymerization of ethylene and vinyl acetate. Generally, the content of vinyl acetate (VA) is about 5-40%. Because vinyl acetate monomer is introduced into the molecular chain, EVA has higher toughness, impact resistance, filler solubility and heat sealing performance. It is widely used in foamed shoe materials, sports goods, functional shed films, packaging films, hot melt adhesives, floor mats, wires and cables, toys and other fields. However, with people's increasing attention to health and environmental protection, the demand for antibacterial and anti-aging properties of EVA foam materials is also increasing.

[0003] In addition, EVA foam material has electrical insulation like most polymer plastics, and its volume resistivity can reach 10 14 Such a high volume resistivity will seriously restrict its application in the packaging of some special products, such as military weapons, electronic components, instruments and other products. Severe static electricity may cause fire. Therefore, it is urgent to study and prepare an antistatic EVA foam material to meet market demand. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide an antistatic EVA foam material and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] An antistatic EVA foaming material comprises the following raw materials in parts by weight: 90-100 parts of EVA, 15-25 parts of ethylene-octene copolymer, 10-18 parts of modified graphene, 2-4 parts of foaming agent, 0.5-1 part of lubricant, 0.5-1 part of zinc oxide and 0.1-0.5 part of crosslinking agent.

[0007] Furthermore, the modified graphene is prepared by the following steps:

[0008] S1. Under nitrogen protection, add 1,3-diamino-2-hydroxypropane, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and DMF (N,N-dimethylformamide) into a dry three-necked flask, stir to dissolve, add EDC (1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride) and NHS (N-hydroxysuccinimide), stir evenly and heat to 50°C, keep warm for 6 hours, cool to room temperature after the reaction, and then distill under reduced pressure to obtain intermediate 1; the amount ratio of 1,3-diamino-2-hydroxypropane, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid, EDC, NHS and DMF is 8.1g:27.1g:0.52g:0.31g:180mL;

[0009] The molar ratio of 1,3-diamino-2-hydroxypropane to 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid is controlled to be 1:1.05-1.1, and the -COOH of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and the -NH2 of 1,3-diamino-2-hydroxypropane undergo amidation reaction under the action of EDC and NHS. The reaction equation is as follows:

[0010]

[0011] S2. Add 2,6-di-tert-butyl-4-bromomethylphenol, intermediate 1 and toluene to a dry three-necked flask under nitrogen protection, stir to dissolve, and then slowly add triethylamine. After the addition is complete, heat to 60°C and stir to react for 3 hours. After the reaction is completed, cool to room temperature and distill under reduced pressure to obtain intermediate 2; the amount ratio of 2,6-di-tert-butyl-4-bromomethylphenol, intermediate 1, triethylamine and toluene is 23.9 g:29.9 g:16.7 mL:240 mL;

[0012] The molar ratio of 2,6-di-tert-butyl-4-bromomethylphenol to intermediate 1 is controlled to be 1:1.05-1.1. Under heating, -NH2 of intermediate 1 and -Br of 2,6-di-tert-butyl-4-bromomethylphenol undergo nucleophilic substitution reaction, and triethylamine is used as an acid binding agent. The reaction process is as follows:

[0013]

[0014] S3, under nitrogen protection, add intermediate 2, tetradecane chloride and DMF into a dry three-necked flask, mix well and then slowly add pyridine, then stir and heat to 75°C for 2h, cool to room temperature after the reaction, and then distill under reduced pressure to obtain intermediate 3; the amount ratio of intermediate 2, tetradecane chloride, pyridine and DMF is 28.4g:29.2mL:9.7mL:180mL;

[0015] The molar ratio of intermediate 2 to tetradecane chloride is controlled to be 1:2.1-2.2. Under heating, -NH- of intermediate 2 and -Cl of tetradecane chloride undergo nucleophilic substitution reaction. Pyridine is used as an acid binding agent. The reaction process is as follows:

[0016]

[0017] S4. The dried three-necked flask was purged with nitrogen for 30 minutes to exclude air and moisture, and then the intermediate 3, KH540 (3-aminopropyltrimethoxysilane), DMF and tetraisopropyl titanate were added in sequence. After stirring evenly, the temperature was raised to 95°C and kept for reaction for 36 hours. After the reaction was completed, it was cooled to room temperature, distilled under reduced pressure, washed with anhydrous ethanol for 3 times, and dried at 80°C for 12 hours. The whole process was carried out under nitrogen protection to obtain intermediate 4; the amount ratio of intermediate 3, KH540, tetraisopropyl titanate and DMF was 39.9 g:8 mL:0.034 g:200 mL;

[0018] The molar ratio of intermediate 3 and KH540 is controlled to be 1:1.1-1.15. Under the catalytic action of tetraisopropyl titanate, the hydroxyl group of intermediate 3 and the silaneoxy group of KH540 undergo the following chemical reaction. The reaction process is shown below:

[0019]

[0020] S5. Add graphene and 65% nitric acid by mass to a three-necked flask, heat to 80°C and stir for 6h. After stirring, cool to room temperature, filter and wash with deionized water until the filtrate is neutral, and dry the residue at 110°C for 12h to obtain pretreated graphene. Add pretreated graphene and deionized water to a dry three-necked flask, stir evenly, and slowly add concentrated hydrochloric acid to adjust the pH value of the system to 5. Then heat to 65°C, add a mixed solution of DMF and intermediate 4, stir and react at 65°C for 10h, finally cool to room temperature, filter, wash with anhydrous ethanol 5 times, and dry at 80°C for 12h to obtain modified graphene. The dosage ratio of graphene to nitric acid is 4g:250mL, and the mass ratio of pretreated graphene to intermediate 4 is 15:1.

[0021] When heated, the trimethoxysilane in the intermediate 4 is hydrolyzed in deionized water and acidic conditions and then condensed to form Si-O-Si and Si-OH, wherein the -OH in the Si-OH forms a hydrogen bond with the -OH on the surface of the pretreated graphene, and then dehydrates and condenses to form a covalent bond, thereby forming a chemical crosslink between the intermediate 4 and the pretreated graphene, thereby greatly reducing the surface energy of the prepared modified graphene. At the same time, the lipophilic benzene ring and long carbon chain in the intermediate 4 are similarly soluble in other raw materials such as EVA and lubricants. Therefore, the interfacial compatibility between the modified graphene and the other raw materials is greatly improved, so that the modified graphene can fully play its role and give the EVA foam material excellent comprehensive properties.

[0022] The graphene in modified graphene is a two-dimensional crystal with only one atomic layer thickness. The electrons in its structure can move freely within the crystal plane. This property helps to quickly dissipate static charge and reduce static electricity accumulation. Secondly, graphene has extremely high electrical conductivity, which can effectively and quickly conduct static electricity and avoid static electricity accumulation. In addition, graphene's ultra-high specific surface area and excellent conductivity make it an ideal antistatic material, which can effectively prevent the generation and accumulation of static electricity in various environments.

[0023] At the same time, graphene has good antibacterial and antiviral capabilities based on the mixed synergistic effect of five mechanisms: physical cutting, membrane surface component extraction, physical capture, oxidative stress and charge conduction.

[0024] The modified graphene surface also has hindered phenol structures and quaternary ammonium salt structures with multiple long carbon chains (14 carbons).

[0025] In the hindered phenol structure, there is a tert-butyl group on each side of the -OH on the benzene ring. Since the hydroxyl group is restricted by spatial barriers, the hydrogen atom can easily fall off from the original molecular structure, thereby achieving the effect of donating protons and combining with peroxy radicals, alkyl radicals, hydroxyl radicals, etc., causing them to lose their original activity, resulting in the termination of the oxygen aging reaction, thereby achieving anti-aging effect and improving the weather resistance of EVA foaming materials.

[0026] The positively charged quaternary ammonium salt structure is adsorbed on the negatively charged bacterial surface through Coulomb force, and then its alkyl chain combines with the cell membrane phospholipid bilayer through hydrophobic interaction, inserting the alkyl chain into and cleaving the cell membrane, causing the leakage of intracellular proteins, DNA, RNA and other substances, thus killing the bacteria. Therefore, the antibacterial activity of the quaternary ammonium salt structure is not only related to N + It is related to the ions and the length of the alkyl chain. When the number of carbon atoms in the alkyl chain is between 10 and 16, the antibacterial property of the quaternary ammonium salt structure is better. When the number of carbon atoms is 14, the antibacterial property of the quaternary ammonium salt structure is the strongest. Therefore, the quaternary ammonium salt structure with a long carbon chain (14 carbons) and graphene work synergistically to give the EVA foam material excellent antibacterial properties.

[0027] In addition, the quaternary ammonium salt structure also has an antistatic effect. The quaternary ammonium part in the quaternary ammonium salt, as a hydrophilic group, carries a positive charge and can interact with moisture (strong polar molecules) in the air to form a conductive continuous film. This film gives the surface of the EVA foam material certain hygroscopicity and ionicity, thereby reducing the surface resistivity and allowing the generated static charge to leak rapidly. The hydrophobic group (long carbon chain) of the quaternary ammonium salt provides lubricity and reduces the friction coefficient, thereby inhibiting and reducing the generation of static charge. This dual action mechanism makes the quaternary ammonium salt structure have an excellent antistatic effect. In addition, with the synergistic effect of graphene, the foam material of the present invention has a stable and excellent antistatic effect.

[0028] Furthermore, the foaming agent is one or both of azodicarbonamide and 4,4'-oxybisbenzenesulfonylhydrazide.

[0029] Furthermore, the lubricant is one or more of stearic acid, zinc stearate, butyl stearate, and magnesium stearate.

[0030] Furthermore, the cross-linking agent is one or both of dicumyl peroxide and dibenzoyl peroxide.

[0031] A method for preparing an antistatic EVA foam material, comprising the following steps:

[0032] Weigh each raw material by weight, then mix them evenly in an internal mixer, mix them in an open mixer, press the materials into thin sheets, and finally place them in a preheated flat vulcanizer mold cavity for mold compression and foaming to obtain an antistatic EVA foam material.

[0033] The beneficial effects of the present invention are as follows: the modified graphene contains a lipophilic long carbon chain and a benzene ring, so it has good compatibility with the remaining raw materials, so that the modified graphene containing graphene, a hindered phenol structure and a quaternary ammonium salt structure of the present invention can be highly dispersed in the EVA foam material and fully exert its effect, so that the EVA foam material of the present invention has efficient and lasting antistatic performance, antibacterial performance and anti-aging performance, and therefore, the application field of the EVA foam material of the present invention is greatly broadened. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] The specific steps for preparing modified graphene are as follows:

[0037] S1. Under nitrogen protection, add 8.1 g of 1,3-diamino-2-hydroxypropane, 27.1 g of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and 180 mL of DMF into a 500 mL dry three-necked flask, stir to dissolve, add 0.52 g of EDC and 0.31 g of NHS, stir evenly, heat to 50°C, keep warm for 6 h, cool to room temperature after the reaction, and then distill under reduced pressure to obtain intermediate 1;

[0038] S2. Under nitrogen protection, add 23.9 g of 2,6-di-tert-butyl-4-bromomethylphenol, 29.9 g of intermediate 1 and 240 mL of toluene to a 500 mL dry three-necked flask, stir to dissolve, and then slowly add 16.7 mL of triethylamine. After the addition is complete, heat to 60 ° C and stir to react for 3 h. After the reaction is completed, cool to room temperature and distill under reduced pressure to obtain intermediate 2;

[0039] S3, under nitrogen protection, add 28.4 g of intermediate 2, 29.2 mL of tetradecane chloride and 180 mL of DMF into a 500 mL dry three-necked flask, mix well, then slowly add 9.7 mL of pyridine, then stir and heat to 75 ° C for 2 h, cool to room temperature after the reaction is completed, and then distill under reduced pressure to obtain intermediate 3;

[0040] S4, purging a 500mL dry three-necked flask with nitrogen for 30min to exclude air and moisture, then adding 39.9g of intermediate 3, 8mL of KH540, 200mL of DMF and 0.034g of tetraisopropyl titanate in sequence, stirring evenly and heating to 95°C for 36h. After the reaction, cooling to room temperature, distilling under reduced pressure, washing with anhydrous ethanol 3 times, and drying at 80°C for 12h. The whole process was carried out under nitrogen protection to obtain intermediate 4;

[0041] S5. Add 4 g of graphene and 250 mL of 65% nitric acid to a 500 mL three-necked flask, heat to 80 ° C and stir for 6 h. After stirring, cool to room temperature, filter and wash with deionized water until the filtrate is neutral, and dry the residue at 110 ° C for 12 h to obtain pretreated graphene; add 3.75 g of pretreated graphene and 200 mL of deionized water to a 500 mL dry three-necked flask, stir evenly and slowly add concentrated hydrochloric acid to adjust the pH value of the system to 5, then heat to 65 ° C, add a mixed solution of 10 mL of DMF and 0.25 g of intermediate 4, stir and react at 65 ° C for 10 h, finally cool to room temperature, filter, wash with anhydrous ethanol 5 times, and dry at 80 ° C for 12 h to obtain modified graphene.

[0042] Example 2

[0043] Preparation of antistatic EVA foam material, the specific steps are as follows:

[0044] 90 parts of EVA, 15 parts of ethylene-octene copolymer, 10 parts of modified graphene obtained in Example 1, 2 parts of azodicarbonamide, 0.5 parts of stearic acid, 0.5-1 parts of zinc oxide, and 0.1 parts of diisopropylbenzene peroxide were weighed by weight, then mixed evenly in an internal mixer, and then mixed in an open mixer. The materials were pressed into thin sheets and finally placed in a preheated flat vulcanizer mold cavity for molded foaming to obtain an antistatic EVA foam material.

[0045] Example 3

[0046] Preparation of antistatic EVA foam material, the specific steps are as follows:

[0047] 98 parts of EVA, 22 parts of ethylene-octene copolymer, 16 parts of modified graphene obtained in Example 1, 3 parts of 4,4'-oxybisbenzenesulfonyl hydrazide, 0.8 parts of zinc stearate, 0.9 parts of zinc oxide, and 0.3 parts of dibenzoyl peroxide were weighed by weight, then mixed evenly in an internal mixer, and then mixed in an open mixer. The materials were pressed into thin sheets and finally placed in a preheated flat vulcanizer mold cavity for molded foaming to obtain an antistatic EVA foam material.

[0048] Example 4

[0049] Preparation of antistatic EVA foam material, the specific steps are as follows:

[0050] 100 parts of EVA, 25 parts of ethylene-octene copolymer, 18 parts of modified graphene obtained in Example 1, 4 parts of 4,4'-oxybisbenzenesulfonyl hydrazide, 1 part of magnesium stearate, 1 part of zinc oxide, and 0.5 part of dibenzoyl peroxide were weighed by weight, then mixed evenly in an internal mixer, and then mixed in an open mixer. The materials were pressed into thin sheets and finally placed in a preheated flat vulcanizer mold cavity for molded foaming to obtain an antistatic EVA foam material.

[0051] Comparative Example 1

[0052] Preparation of EVA foam material, the specific steps are as follows:

[0053] The remaining steps remained unchanged, except that the modified graphene in Example 4 was replaced by 16.9 parts of untreated graphene, 0.7 parts of antioxidant 1010 and 0.4 parts of didodecyldimethylammonium chloride to prepare an EVA foam material.

[0054] Comparative Example 2

[0055] Preparation of EVA foam material, the specific steps are as follows:

[0056] The remaining steps remained unchanged, except that the modified graphene in Example 4 was replaced by 16.9 parts of polyethylene oxide, 0.7 parts of antioxidant 1010 and 0.4 parts of didodecyldimethylammonium chloride to prepare an EVA foam material.

[0057] Performance Testing

[0058] The surface resistivity of the EVA foam materials obtained in Examples 2-4 and Comparative Examples 1-2 was tested with reference to GB / T1410-2006 "Test Method for Volume Resistivity and Surface Resistivity of Solid Insulating Materials"; the tensile strength and elongation at break of the EVA foam materials obtained in Examples 2-4 and Comparative Examples 1-2 were tested with reference to GB / T6344-1996 "Determination of Tensile Strength and Elongation at Break of Soft Foam Polymer Materials"; and the EVA foam materials were subjected to wet heat aging for 72 hours at 110°C and 60% humidity, and the tensile strength and elongation at break were tested according to the corresponding standards to check the anti-aging performance of the EVA foam materials. The test results of all items are shown in Table 1 below:

[0059] Table 1

[0060]

[0061] The antibacterial properties of the EVA foam materials prepared in Examples 2-4 and Comparative Examples 1-2 were tested with reference to QB / T2591-2003 "Antibacterial Plastics - Antibacterial Performance Test Methods and Antibacterial Effects". The test results are shown in Table 2 below:

[0062] Table 2

[0063]

[0064] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0065] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. An antistatic EVA foam material, characterized in that: The invention comprises the following raw materials in parts by weight: 90-100 parts of EVA, 15-25 parts of ethylene octene copolymer, 10-18 parts of modified graphene, 2-4 parts of foaming agent, 0.5-1 parts of lubricant, 0.5-1 parts of zinc oxide, and 0.1-0.5 parts of cross-linking agent; Wherein, the modified graphene is prepared by the following steps: S1. Under nitrogen protection, 1,3-diamino-2-hydroxypropane, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and DMF were added to a flask, and EDC and NHS were added after stirring. The mixture was reacted at 50° C. for 6 h, cooled, and distilled under reduced pressure to obtain intermediate 1. S2. Add 2,6-di-tert-butyl-4-bromomethylphenol, intermediate 1 and toluene into a flask under nitrogen protection, add triethylamine after stirring, react at 60° C. for 3 h, and distill under reduced pressure to obtain intermediate 2; S3, under nitrogen protection, add intermediate 2, tetradecane chloride and DMF into a flask, add pyridine after mixing, react at 75°C for 2h, cool, and distill under reduced pressure to obtain intermediate 3; S4, after nitrogen blowing into the flask, add intermediate 3, KH540, DMF and tetraisopropyl titanate, react at 95°C for 36h, cool, distill under reduced pressure, wash and dry to obtain intermediate 4; S5. Add graphene and 65wt% nitric acid to a flask, stir at 80°C for 6h, cool, filter, wash, and dry the residue to obtain pretreated graphene; add pretreated graphene and deionized water to a flask, add concentrated hydrochloric acid to adjust the pH value of the system to 5, heat to 65°C, add DMF and intermediate 4, react at 65°C for 10h, cool, filter, wash, and dry the residue to obtain modified graphene.

2. The antistatic EVA foam material according to claim 1, characterized in that: The usage ratio of 1,3-diamino-2-hydroxypropane, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid, EDC, NHS and DMF in step S1 is 8.1 g:27.1 g:0.52 g:0.31 g:180 mL.

3. The antistatic EVA foam material according to claim 1, characterized in that: The usage ratio of 2,6-di-tert-butyl-4-bromomethylphenol, intermediate 1, triethylamine and toluene in step S2 is 23.9 g:29.9 g:16.7 mL:240 mL.

4. The antistatic EVA foam material according to claim 1, characterized in that: The usage ratio of intermediate 2, tetradecane chloride, pyridine and DMF in step S3 is 28.4 g: 29.2 mL: 9.7 mL: 180 mL.

5. The antistatic EVA foam material according to claim 1, characterized in that: The usage ratio of intermediate 3, KH540, tetraisopropyl titanate and DMF in step S4 is 39.9 g:8 mL:0.034 g:200 mL.

6. The antistatic EVA foam material according to claim 1, characterized in that: The usage ratio of graphene and nitric acid in step S5 is 4 g:250 mL, and the mass ratio of pretreated graphene to intermediate 4 is 15:

1.

7. The antistatic EVA foam material according to claim 1, characterized in that: The foaming agent is one or two of azodicarbonamide and 4,4'-oxybisbenzenesulfonyl hydrazide.

8. The antistatic EVA foam material according to claim 1, characterized in that: The lubricant is one or more of stearic acid, zinc stearate, butyl stearate and magnesium stearate.

9. The antistatic EVA foam material according to claim 1, characterized in that: The cross-linking agent is one or both of dicumyl peroxide and dibenzoyl peroxide.

10. The method for preparing an antistatic EVA foam material according to claim 1, characterized in that: Prepared by the following steps: Weigh each raw material by weight, then mix them evenly in an internal mixer, mix them in an open mixer, press the materials into thin sheets, and finally place them in a preheated flat vulcanizer mold cavity for mold compression and foaming to obtain an antistatic EVA foam material.

Citation Information

Patent Citations

  • Polycarbonate / polypropylene alloy material and preparation method thereof

    CN113943458A

Cited By

  • A graphene antistatic PC composite material and preparation method thereof

    CN119752147A

  • EVA (Ethylene Vinyl Acetate) foaming material, preparation method and application thereof

    CN121086320A